2013 IEEE/AIAA 32nd Digital Avionics Systems Conference (DASC) 2013
DOI: 10.1109/dasc.2013.6712530
|View full text |Cite
|
Sign up to set email alerts
|

An operational safety and certification assessment of a TASAR EFB application

Abstract: This paper presents an overview of a Traffic Aware Strategic Aircrew Requests (TASAR) Electronic Flight Bag application intended to inform the pilot of trajectory improvement opportunities while en route that result in operational benefits. The results of safety analyses and a detailed review of Federal Aviation Administration (FAA) regulatory documents that establish certification and operational approval requirements are presented for TASAR.The safety analyses indicate that TASAR has a likely Failure Effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…2,3 Since 2012, NASA has been developing and testing the TASAR concept with the goal of providing an application that could be used by operators in the current-day NAS to optimize their flights. Early activities have included a formal definition of the concept 12 , an assessment of Federal Aviation Administration (FAA) certification and operational approval requirements, 13,14 and a preliminary benefits analysis. The results of the benefits analysis indicated that aircraft equipped with TASAR capabilities could reduce flight travel time from one to four minutes and fuel burn by 50 to 550 pounds.…”
Section: Tasar Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Since 2012, NASA has been developing and testing the TASAR concept with the goal of providing an application that could be used by operators in the current-day NAS to optimize their flights. Early activities have included a formal definition of the concept 12 , an assessment of Federal Aviation Administration (FAA) certification and operational approval requirements, 13,14 and a preliminary benefits analysis. The results of the benefits analysis indicated that aircraft equipped with TASAR capabilities could reduce flight travel time from one to four minutes and fuel burn by 50 to 550 pounds.…”
Section: Tasar Conceptmentioning
confidence: 99%
“…This read-only access to avionics data allows TAP to be classified as a system that has minor or no effect to safety-critical operations, further streamlining the process of FAA approval. 13,14 The TAP system has been developed to operate on a variety of EFB platforms and test configurations (See Fig. 2) using a single code base:…”
Section: A Platformmentioning
confidence: 99%
“…The analysis was documented and presented in 2013 12 and further documented in 2015. 13 These references identify 17 regulations, standards, and guideline documents that were reviewed for this analysis, many of which relate to the design and installation of EFB hardware and associated software applications.…”
Section: Certification and Operational Approval Requirements Analysismentioning
confidence: 99%
“…8,11,12,13 Two safety assessment methodologies compliant with the FAA's Safety Management System were used to determine the Failure Effects Classification (FEC) of TASAR. Method 1, based on ARP 4761 [14], AC 23-1309 [15] and AC 25-1309 [16] for Part 23 and Part 25 aircraft operations, is a traditional system safety process for airborne systems, e.g., TASAR.…”
Section: Safety and Operational Hazards Assessmentmentioning
confidence: 99%
“…The primary purpose for flight-testing TAP was to bridge the critical divide between Technology Readiness Level (TRL) 4 (testing in a laboratory environment) and TRL 6 (testing in a relevant environment), as a steppingstone to full operational deployment (TRL 9). Since the TASAR concept is intended to provide near-term operational benefits, NASA has undertaken a number of activities to accelerate its adoption by the operator community: NASA has analyzed the potential user benefits 4 , the operational hazards 5 , and the Federal Aviation Administration (FAA) certification and operational approval requirements 5 for TASAR. NASA has developed the TAP software application and has evaluated the human-machine interface (HMI) in a high-fidelity fixed-base flight simulator during a human-in-the-loop experiment with active airline pilots 6 .…”
Section: A Flight Trial Rationalementioning
confidence: 99%